Gut microbiota alterations from different Lactobacillus probiotic-fermented yoghurt treatments in slow-transit constipation. (November 2017) - Liu, Chen-Jian; Tang, Xiao-Dan; Yu, Jie; Zhang, Hai-Yan; Li, Xiao-Ran
Highlights: A new yoghurt could improve defecation time and intestinal health obviously. A new formulation was composed of Lac. lactis, Lb. plantarum and Lb. casei . Yogurt is excellent functional foods to improve symptoms of constipation. Yoghurt intake could change intestinal bacterial community composition. Abstract: Constipation is a frequent complaint, and probiotics could have a potentially synergistic effect on intestinal transit. In the present study, yoghurt intake improved the symptoms of slow-transit constipation, which was confirmed in 144 mice (nine groups, n = 16) with loperamide-induced constipation. Yoghurt fermented with different probiotics was administered orally. Loperamide treatment caused a marked increase in first defecation time and a decrease in the charcoal transit ratio (P < 0.05), while loperamide treatment after intake of a new formulation of yoghurt could significantly improve defecation time and intestinal health. Significant ( P  < 0.001) decreases in butanoic acid content were observed in groups given three different strains of yoghurt. Yoghurt intake could also change the intestinal bacterial community composition, which was supported by operational taxonomic unit-related analysis as well as principal coordinates analysis (PCA). Our results showed conclusive evidence indicating that yogurt is an excellent functional food that improves the symptoms of slow-transit constipation.